Managing customer experiences in an omnichannel world : melody of online and offline environments in the customer journey - Dirsehan, Taşkın, 1985- (Emerald Publishing Limited, 2020)
In a typical day, a customer's journey moves from a physical to a digital environment multiple times, to successfully and effectively manage a customer's experience organizations need to integrate both these environments in an omnichannel way. This edited book examines customer journeys, omnichannel retailing, digital and mobile marketing, augmented and virtual reality, gamification, artificial intelligence in marketing, blockchain applications and more to provide theoretical and practical methods of impact for businesses. The book provides insights for researchers and practitioners in the areas of marketing, digitalisation, service operations, management, communication, administrative sciences and more. The chapters intersect methodology, research, theory and applications all along the customer journey and customer touchpoints through digital and physical environments. Increasing technological developments and the wider integration of the Internet of Things will make the need for smooth omnichannel management for customers and consumers ever more important for organizations and a key factor of successful business strategy.
Includes index.
Keywords: Consumer behavior.; Marketing -- Technological innovations.; Business & Economics -- Marketing -- General.; Sales & marketing management.; elektronické knihy; electronic books